Targeted Lung Deposition From Nebulization Is Not Improved in the Lateral Decubitus Position in Healthy Volunteers. - Reychler, Gregory; San Miguel-Pagola, Marta; Aubriot, Anne-Sophie; Herrero-Cortina, Beatriz; Lecocq, Vinciane; Hesse, Michel; Liistro, Giuseppe; Jamar, Fran¸ois (Respiratory Care, 2019)
BACKGROUND: Clinical benefits of inhaled therapies are related to the amount of drug deposited in the targeted area of the lung. Body positions that influence the distribution of lung ventilation should impact lung deposition of the nebulized drug. The aim of this study was to analyze the immediate effect of body position while the subject lies on his side (lateral decubitus) during nebulization on 3-dimen- sional total and regional lung deposition. METHODS: A randomized crossover trial was performed on healthy male volunteers without cardiovascular or pulmonary disease. A technetium-99m diethylene- triaminepentaacetic acid (99mTc-DTPA) solution (4 mL) was nebulized using an individual-controlled inhalation system in left lateral decubitus and sitting positions with a 96-h washout period (43 inspira- tions of 4 s [ie, drug delivered until second 3] with a tidal volume of 0.8 L and a low inspiratory flow (200 mL/s). Drug deposition was followed with the use of planar images and single-photon-emission computed tomography combined with low-resolution computed tomography. Total and regional depo- sitions were the main outcomes. Penetration index was also considered. RESULTS: Six participants (26.8 ± 6.9 y old) were included. Total lung deposition tended to be higher in a sitting position than in a lateral decubitus position: 10.2 ± 0.9% of nominal dose (95% CI 9.1-11.3) vs 8.6 ± 1.4% of nominal dose (95% CI 6.8-10.4) (P = .09). The deposition was significantly reduced in the dependent (left) lung in the lateral decubitus position: 3.5 ± 0.7% of nominal dose (95% CI 2.6-4.3) vs 4.7 ± 0.3% of nominal dose (95% CI 4.3-5.0) (P = .03). Penetration index was only influenced by body position for the dependent (left) lung (P = .043). CONCLUSIONS: The total amount of drug delivered to the lungs during nebulization with an individual-controlled inhalation system tended to decrease when performed in the left lateral decubitus position. Moreover, contrary to the initial hypothesis, the deposition of particles in the dependent lung was not improved by the lateral decubitus position in this configuration. (ClinicalTrials.gov registration NCT02451501.)